Merdeka Belajar: Solusi Revolusi Pendidikan di Indonesia - Miftah Fadhillah; Masduki Asbari; Eiffeline Melati Octhaviani (Journal of Information Systems and Management (JISMA), 2024)
The aim of this study is to respond to education problems in Indonesia which is experiencing a learning crisis. This study report uses a qualitative method by taking notes because the data source was obtained by listening to oral narratives from the Indonesian Ministry of Education and Culture's Youtube channel entitled "Freedom to Learn: Lessons from the Transformation of Indonesian Education". The results of this study explain how efforts have been made to improve the quality of the education system in Indonesia and make the learning process an interesting and enjoyable experience. This research was conducted because of the gap between education in the regions and education in the city.